2021
DOI: 10.1152/ajpheart.00957.2020
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte-specific deletion of HuR induces spontaneous cardiac hypertrophy and fibrosis

Abstract: Adipose tissue homeostasis plays a central role in cardiovascular physiology, and the presence of thermogenically active brown adipose tissue (BAT) has recently been associated with cardiometabolic health. We have previously shown that adipose tissue-specific deletion of HuR (Adipo-HuR-/-) reduces BAT-mediated adaptive thermogenesis, and the goal of this work was to identify the cardiovascular impacts of Adipo-HuR-/-. We found that Adipo-HuR-/- mice exhibit a hypercontractile phenotype that is accompanied by i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 86 publications
2
13
0
Order By: Relevance
“…RNA sequencing of paired end 100bp reads at a depth of ~30M reads/sample was performed by the Cincinnati Children’s Hospital Medical Center DNA Sequencing and Genotyping Core. Sequence read mapping and differential expression analysis was done using CLC Genomics Workbench v21.0.3 (Qiagen) as we have done previously [3,16,24]. The single cell RNA-seq dataset using isolated fibroblasts from post-MI hearts has been previously described and is publicly available (NCBI GEO Database accession GSE83337) [25].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…RNA sequencing of paired end 100bp reads at a depth of ~30M reads/sample was performed by the Cincinnati Children’s Hospital Medical Center DNA Sequencing and Genotyping Core. Sequence read mapping and differential expression analysis was done using CLC Genomics Workbench v21.0.3 (Qiagen) as we have done previously [3,16,24]. The single cell RNA-seq dataset using isolated fibroblasts from post-MI hearts has been previously described and is publicly available (NCBI GEO Database accession GSE83337) [25].…”
Section: Methodsmentioning
confidence: 99%
“…The single cell RNA-seq dataset using isolated fibroblasts from post-MI hearts has been previously described and is publicly available (NCBI GEO Database accession GSE83337) [25]. Correlation analysis of gene co-expression within this dataset was done using transcriptome-wide Pearson correlation (statistical significance cutoff at P ≤ 0.05) modified from the WGCNA R-package (R v4.1.0) as previously described [24,26]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HuR is significantly accumulated in stimulated human lung fibroblasts, IPF lungs and mouse lungs of experimental pulmonary fibrosis; HuR knockdown affected the mRNA stability of ACTA2 36 . However, despite numerous studies are favoring the profibrotic role of HuR, recent studies also show that HuR might serve as protective factors against cardiac remodeling and liver fibrosis 37,38 . Therefore, it still warrants for further investigation about the sophisticated molecular function, the post-translational modification as well as the druggability of HuR in pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…This work is also of particular interest to my laboratory as we recently demonstrated that adipocyte-specific deletion of the RNA binding protein HuR (Adipo-HuR −/− ) elicits spontaneous cardiac hypertrophy and fibrosis ( 18 ), and additionally have expertise in the field of cardiac preconditioning ( 19 ) and ischemic injury ( 20 , 21 ). Results from our Adipo-HuR −/− mice are suggestive of an endocrine EV driven mechanism of cardiac pathology, and work is ongoing to characterize the HuR-dependent cargo loading of Adipo-EVs from these mice, but given its nature as an RNA binding protein, the mediating factors are likely to be RNA.…”
mentioning
confidence: 99%